2022
DOI: 10.11648/j.bs.20220801.14
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia and Its Correlates Among Nigerian SARS-CoV-2 Infected Patients

Abstract: Background: Disorders of electrolytes balance, especially that of potassium, have frequently been documented among patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, most of these reports have been documented among the western populations. Hence, this current study was aimed to evaluate the pattern of derangement in potassium balance and its correlation to other clinical and laboratory variables among Nigerians. Methods: Archived data of all eligible adult patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Data from recent studies indicate that derangement in sodium status tends to correlate significantly with the extent of SARS-CoV-2-induced pulmonary dysfunctions [14]- [16]. However, most of these previous studies were mostly reported among Caucasians [7], [8]. Racial background is a major determinant of SARS-CoV-2 pathophysiology [15], [17], consequently, conclusions from these previous studies may not reflect populations of Negroid race.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Data from recent studies indicate that derangement in sodium status tends to correlate significantly with the extent of SARS-CoV-2-induced pulmonary dysfunctions [14]- [16]. However, most of these previous studies were mostly reported among Caucasians [7], [8]. Racial background is a major determinant of SARS-CoV-2 pathophysiology [15], [17], consequently, conclusions from these previous studies may not reflect populations of Negroid race.…”
Section: Introductionmentioning
confidence: 95%
“…Among the biochemical abnormalities frequently reported is the derangement in water-electrolyte balance especially those of sodium disorders which have been reported in association with adverse outcomes of the disease [7]- [13]. Data from recent studies indicate that derangement in sodium status tends to correlate significantly with the extent of SARS-CoV-2-induced pulmonary dysfunctions [14]- [16].…”
Section: Introductionmentioning
confidence: 99%